Moringa cultivation in semi-arid regions: A sustainable solution to malnutrition - Kumar, Vipin; Gairola, Ananya; Kumar, Sandesh; Babu, Subhash; Rathore, S. S. (Indian Horticulture, 2025)
Achieving the targets outlined in Sustainable Development Goal 2 (SDG 2) by 2030 may seem challenging, necessitating nothing less than a miraculous intervention. Fortunately, such a miracle exists in the form of Moringa oleifera, commonly known as the Miracle Tree. Originally native to India, it is now cultivated across tropical and sub-tropical regions of Asia, Africa, and Latin America. This remarkable tree, often dubbed as the Tree of Life, offers a range of benefits as every part of it holds value and utility, making it one of the most nutrient-rich plants known. Moringa oleifera is highly valued as a fundamental dietary component, often recognized as the ‘native nourishment of tropical regions’. Nearly all components of the plant, spanning from its roots, bark, gums, leaves, fruits (pods), flowers, seeds, to seed oil, are utilized in diverse traditional medicinal practices throughout South Asia. With Moringa oleifera at our disposal, we can address not only hunger and malnutrition, the primary objectives of SDG 2, but also make strides toward achieving other Sustainable Development Goals.